The L-Type Amino Acid Transporter LAT1—An Emerging Target in Cancer - Häfliger, Pascal (Int J Mol Sci, 2019)
Chronic proliferation is a major hallmark of tumor cells. Rapidly proliferating cancer cells are highly dependent on nutrients in order to duplicate their cell mass during each cell division. In particular, essential amino acids are indispensable for proliferating cancer cells. Their uptake across the cell membrane is tightly controlled by membrane transporters. Among those, the L-type amino acid transporter LAT1 (SLC7A5) has been repeatedly found overexpressed in a vast variety of cancers. In this review, we summarize the most recent advances in our understanding of the role of LAT1 in cancer and highlight preclinical studies and drug developments underlying the potential of LAT1 as therapeutic target.